STATISTICAL AND ANALYTICAL SUPPORT OF THE PERSONNEL MANAGEMENT SYSTEM OF ENTERPRISES AND ORGANIZATIONS (Regional aspects of productive forces development of Ukraine, 2024)
ABSTRACTIntroduction. Effective personnel management is a key factor in the competitiveness of enterprisesand organizations, as it affects their productivity, innovative development and adaptability to marketchanges. The use of statistical and analytical support in the personnel management system allows formaking informed management decisions, increasing the efficiency of personnel work and optimizingpersonnel policy. However, many enterprises and organizations face difficulties in implementing suchmethods due to insufficient automation of data collection processes, limited analytical tools and the lackof a single methodological base.Research purpose and methods. The purpose of the article is to determine the essence and placeof statistics and analytics in the management system of enterprises and organizations, to substantiate thetheoretical and methodological principles of using statistical and analytical tools and systems to optimizepersonnel processes and to develop practical recommendations for improving the statistical andanalytical support of personnel management. The study uses general scientific and special methods, inparticular analysis and synthesis, scientific abstraction, system analysis, comparative analysis,generalization, as well as methods of synthesis, induction and deduction for a comprehensive assessmentof the statistical and analytical support of personnel management and the formulation ofrecommendations for its improvement.Results. The article considers the concept of personnel management and its role in the generalmanagement system of enterprises and organizations. The focus is on the growing role of statistical andanalytical support of personnel management, its feasibility is substantiated and the importance of usingHR statistics and analytics to increase the efficiency of enterprises and organizations. The role and maindirections of application of statistical and analytical tools in personnel management are defined anddetailed. The main problems that arise when integrating statistics and analytics into the personnelmanagement system are identified and characterized. The directions for improving the personnelmanagement process based on modern statistical and analytical methods are substantiated.Conclusions. The implementation of statistical and analytical support allows to significantlyimprove the efficiency of personnel management due to objective monitoring of personnel processes,increasing the accuracy of forecasting changes in the personnel structure and optimizing the decisionmakingprocess. For the successful integration of analytical methods into the personnel policy ofenterprises and organizations, it is necessary to automate the collection and analysis of statistical data,train specialists with appropriate competencies and develop methodological foundations for the effectiveuse of HR analytics.Keywords: personnel management, HR manager, statistics, analytics, statistical analysis,statistical data, HR analytics, personnel statistics.